2008
DOI: 10.1002/cmdc.200800192
|View full text |Cite
|
Sign up to set email alerts
|

Norcantharidin Analogues: Synthesis, Anticancer Activity and Protein Phosphatase 1 and 2A Inhibition

Abstract: Cantharidin (1) and its derivatives are of significant interest as serine/threonine protein phosphatase 1 and 2A inhibitors. Additionally, compounds of this type have displayed growth inhibition of various tumour cell lines. To further explore both of these inhibition pathways, a number of amide-acid norcantharidin analogues (15-26) were prepared. Compounds 23 and 24, containing two carboxylic acid residues, showed good PP1 and PP2A activity, with IC(50) values of approximately 15 and approximately 3 mum, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…8,21,22 PP2B, also known as CaN, is the only Ca 2 þ and calmodulin-dependent Ser/Thr protein phosphatase ubiquitously expressed and is highly conserved in eukaryotes. CaN consists of two subunits: the enzymatic subunit A (CaN A) and the regulatory subunit B (CaN B).…”
Section: Effects Of Can Sirna On Can Mrna and Protein Expression Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…8,21,22 PP2B, also known as CaN, is the only Ca 2 þ and calmodulin-dependent Ser/Thr protein phosphatase ubiquitously expressed and is highly conserved in eukaryotes. CaN consists of two subunits: the enzymatic subunit A (CaN A) and the regulatory subunit B (CaN B).…”
Section: Effects Of Can Sirna On Can Mrna and Protein Expression Of Hmentioning
confidence: 99%
“…(3) It has been reported that NCTD inhibited not only PP2B but also PP1 and PP2A. 8,22 CsA, however, forms complexes with immunophilins that exert their selective inhibitory action on PP2B. PP1, PP2A, and PP2B all belong to the PPP family of Ser/Thr protein phosphatases and participate in regulating many important physiological processes, such as glycogen metabolism, cell apoptosis, and gene transcription.…”
Section: Effects Of Can Sirna On Can Mrna and Protein Expression Of Hmentioning
confidence: 99%
“…As shown in Scheme 1, the target compounds II were synthesized by the aminolysis reaction of NCTD I and various halogen aromatic amines in the presence of triethylamine as the binding acid agent, and synthesized via decomposing the anhydride ring of NCTD I by a halogenated aniline with different electronegativity [28].…”
Section: Chemistrymentioning
confidence: 99%
“…Significant effort has been devoted to synthesizing norcantharidin analogs with low toxicity for development as selective phosphatase inhibitor drugs (McCluskey et al, 2000;Hill et al, 2007aHill et al, ,b, 2008. These studies have generated numerous compounds, including the most potent PP2A-and PP1-selective analogs described to date, which have 5-to 15-fold greater potency for growth inhibition (GI 50 ϳ9.6 and ϳ3.3 M, respectively) in several human cancer cell lines compared with norcantharidin (GI 50 ϳ45 M) (Hill et al, 2007b).…”
Section: Pp2a/pp1 Catalytic Subunits As Drug Targetsmentioning
confidence: 99%